Modelling and control of grid connected microgrid with hybrid energy storage system - Suganthi Neelagiri; Pasumarthi Usha (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
This paper presents a photovoltaic (PV) microgrid with battery and super capacitor hybrid energy storage systems. The proposed microgrid system is designed for both grid connected and standalone mode with coordinated control-based energy management system, which controls DC link voltage, voltage and frequency balance at point of common coupling. DC link voltage control is implemented using dual loop PI controller-based voltage controller and inverter control is based on D-Q reference frame technique. The microgrid system is demonstrated in MATLAB/Simulink. The presentation of the planned energy supervision system is analyzed for varying generation and load condition. In the proposed microgrid the battery energy storage system is utilized to provide long term energy during average power requirement and supercapacitor energy storage system is utilized to provide short term power requirements during sudden load variation, generation variation and during transition of modes. Designed energy management system performs effectively in grid connected mode, standalone mode with smooth transition between the modes. And it maintains dc bus voltage of the microgrid constant irrespective of load and generation variations and also during mode changing conditions.